Biomechanical Features of Backstroke to Breaststroke Transition Techniques in Age-Group Swimmers - Chainok, Phornpot; de Jesus, Karla; Mourão, Luis; Fonseca, Pedro Filipe Pereira; Zacca, Rodrigo; Fernandes, Ricardo J.; Vilas-Boas, João Paulo (Frontiers in Sports and Active Living, 2022)
The aim of this study was to identify the biomechanical features of backstroke-to-breaststroke transition techniques (open, somersault, bucket and crossover) in age-group swimmers. Eighteen pre-adolescent swimmers (12.2 ± 0.4 years old and 3-4 Tanner stages) underwent four weeks systematic contextual interference training, comprising 16 sessions (40 minsession-1). Soon after, an experimental testing was conducted where swimmers randomly performed 12 x 15-m maximal turns (composed by 7.5m turn-in and 7.5 m turn-out of the wall segments), three in each transition technique. Kinematical, kinetic and hydrodynamic variables were assessed with dual-media motion capture system (12 land and 11 underwater cameras), tri-axial underwater force plates and inverse dynamics. Variables were grouped in turn-in (approach and rotation) and turn-out (wall contact, gliding and pull-out) phases, with factor analysis used to select the variables entering on multiple regressions. For the turn-in phase, 86, 77, 89 and 87% of variance for open, somersault, bucket and crossover turning techniques (respectively) was accounted by the 7.5 and 2.5 m times, mean stroke length and rotation time. For the turn-out phase, first gliding distance and time, second gliding depth, turn-out time, and dominating peak_Z push-off force accounted for 93 % in open turn, while wall contact time, first gliding distance, breakout distance and time, turn-out time, dominating peak_Y push-off force, and second gliding drag coefficient accounted for 92 % in a somersault turn. The foot plant index, push-off velocity, second gliding distance and turn-out time accounted for 92% in bucket turn while breakout and turn-out time, non-dominating peak_Y and peak_Z push-off force, first and second gliding drag force and second gliding drag coefficient accounted for 90 % in crossover turn, respectively. The findings in this study were novel and provide relevant biomechanical contribution, focusing on the key kinematic–temporal determinant during turn-in, rotation, and push-off efficacy, as well as the kinetic and hydrodynamic during turn-out, which would lead to improved backstroke-to-breaststroke transition techniques in 11–13-year-old age-group swimmers.